Covid-induced thyroiditis - Ghaffar, Tahir; Bakht Babar; Mian Sameer Ahmad; Adnan Rahman; Sabeen Zia; Azizul Hasan Aamir (Journal of the Pakistan Medical Association, 2022)
Thyroiditis is one of the manifestations of novel Covid-19 virus. Thyroid function test (TFTs) shows typical features of hyperthyroidism. Inflammatory markers and thyroid scan give clue to the diagnosis. This report is about a 39-year-old female who presented with signs and symptoms of thyrotoxicosis along with pain in the neck, odynophagia, and intermittent fever after recovering from Covid-19 a few weeks back. She had no significant history of past medical or endocrine disease. TFTs revealed high T3 and T4 and low TSH. Thyroid scan revealed decrease uptake and ESR was 115. She was started on NSAID, steroids, and beta blocker. Four weeks later, she reverted with the resolution of symptoms and normal TFTs. Keywords: Covid-19, thyroiditis.